Meteorological Wind Effect on the Ballistic Trajectory of a Medium Calibre System - Knight, Daniel (Cranfield University, 2020)
Modern systems use a single wind sensor onboard the vehicle to measure and capture meteorological wind data to calculate a weapon systems ballistic offset. The most calculations assumes constant wind between firing point and target for the offset. Meteorological wind is not constant being effect by wind gradient, terrain height and other surface changes. Using trial and test data from multiple wind sensors on a firing range, the wind can be modelled across the full flight of a rounds trajectory. Using modelling and analytical approaches to test known and experimental theories around meteorological wind offset to ballistic trajectory. The modelling provides a cost effective approach alongside practical real data from testing.
Keywords: 'DSDS20 Poster'; 'DSDS20'; 'Ballistics'; 'Meteorological Wind'; 'Fire Control'; 'Meteorology'; 'Defence Studies'